Rekayasa Dosis Nutrisi Melalui Drip Irrigation System terhadap Produksi Tomat Cherry (Solanum pimpinellifolium) Lokal Subang - Enceng Sobari (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Tomatoes are easily damaged horticultural products, so that further handlings are needed in food production in the industry today. In order to keep availability, there is an increase in tomato fruit volume as raw material. Among them with increasing types and varieties of tomatoes that need to be continuously developed to supply the industry's needs. The research aimed to increase local tomato cherry production in Subang through an engineering strategy of nutrient feeding with a drip irrigation system. Research conducted from April to December 2019 at Cigadung Subang, West Java. The research was conducted using the Completely Randomized Design (CRD) one factor and the Duncan’s test at 7 nutritional dose treatment consists of P1 = dose 5 ml, P2 = dose 7 ml, P3 = dose 10 ml, P4 = dose 15 ml, P5 = dose 20 ml, P6 = dose 25 ml, P7 = Control with 5 repetition. The results concluded that two applications of nutritional doses at 7 and 10 ml could give different responses that increase the diameter and thickness of the fruits.